2000
DOI: 10.1055/s-2000-7439
|View full text |Cite
|
Sign up to set email alerts
|

Verletzungsmuster und -prophylaxe beim Gleitschirmfliegen

Abstract: This study will present trends and recommendations to increase active and passive safety in paragliding on the basis of current state-of-the-art equipment and typical patterns of injury. This German-Swiss teamwork presents data of 55 male and 9 female patients treated after paragliding accidents between 1994 to 1998 respectively 1996 to 1998. 43.7% of the pilots presented with multiple injuries, 62.5% suffered spinal fractures and 18.8% pelvic fractures. 28.4% of the injured pilots were admitted with injuries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 4 publications
1
9
0
6
Order By: Relevance
“…Back protection has been required by law since 1 January 1998 in Austria and 1 January 2000 in Germany. The large percentage (21.6%) of sideways crash landings, as well as the complex pattern of injuries in the mostly unstable pelvic fractures shown by a recent study, 8 corroborate the current development of side protectors.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Back protection has been required by law since 1 January 1998 in Austria and 1 January 2000 in Germany. The large percentage (21.6%) of sideways crash landings, as well as the complex pattern of injuries in the mostly unstable pelvic fractures shown by a recent study, 8 corroborate the current development of side protectors.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast with early studies, 5 9 which predominantly reported accidents in trainee pilots, the number of such accidents had already fallen to 50% in 1990. 3 In a study of 1994-1998 or 1996-1998, such accidents represented just 7.5% of all accidents 8 and in this study 16%. These values confirm the appreciable qualitative improvement in training, the practical sections of which are now mostly carried out with the help of radio.…”
Section: Discussionmentioning
confidence: 49%
“…This injury pattern, reflecting mainly vertical forces, is significantly different from the pattern with inversed distribution identified in our series, in which vertebral fractures predominated and were combined with lower limb fractures in 13 pilots (35%). We interpret this inversion of frequencies, also reported in a recent study, 8 and the high percentage of combined spine and lower limb fractures as a result of additional shear forces.…”
Section: Discussionmentioning
confidence: 49%
“…[1][2][3]5,6,8,28 In the same series, injuries to the spine were diagnosed with a similar frequency of 20% to 63%, and the combination of spine and lower limb fractures was mentioned. In the present study, we identified this combination in paragliding accidents with SCI as a most characteristic injury pattern when compared to other traumatic lesions leading to paraplegia or tetraplegia (P Ͻ 0.001).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation